Relations Attitude Towards Mathematics Lessons: Anxiety and Academic Success - Tuncer, Murat; Yilmaz, Omer (Hipatia Press, 2020)
In this particular study attitude towards mathematics lessons and relation between anxiety and academic success had been explored. Though as a result of the comparative analysis of the study gender, teacher, class and the most popular and favourite lesson were determined to cause significant differences of opinion with regard to attitude towards mathematics lesson in some cases, based on structural equation modelling substantive and significant impact had been observed only for the most popular and favourite lesson. Besides, anxiety towards mathematics lesson was determined to have a mediation impact on the relation between attitude towards mathematics lesson and anxiety. The most popular and favourite lesson variable differentiated academic success in a significant manner. In the meantime, a significant relation was determined between attitude as a scaling factor and success in mathematics lesson. Anxiety had been determined to be effective is projection and prediction of success with its intermediary impact.
Keywords: Attitude towards mathematics lesson; anxiety towards mathematics lesson; success in mathematic lesson